Application of a Hyperelastic 3D Printed Scaffold for Mesenchymal Stem Cell-Based Fabrication of a Bizonal Tendon Enthesis-like Construct - Gottardi, Riccardo; Moeller, Kim; Di Gesù, Roberto; Tuan, Rocky S.; van Griensven, Martijn; Balmayor, Elizabeth R. (Frontiers in Materials, 2021)
After surgical tendon repair, the tendon-to-bone enthesis often does not regenerate, which leads to high numbers of rupture recurrences. To remedy this, tissue engineering techniques are being pursued to strengthen the interface and improve regeneration. In this study, we used hyperelastic biphasic 3D printed PLGA scaffolds with aligned pores at the tendon side and random pores at the bone side to mimic the native insertion side. In an attempt to recreate the enthesis, the scaffolds were seeded with adult human mesenchymal stem cells and then cultured in dual fluidic bioreactors, which allows the separate in-flow of tenogenic and chondrogenic differentiation media. MTS assay confirmed the ability of cells to proliferate in dual-flow bioreactors at similar levels to tissue culture plate. Hematoxylin-eosin staining confirmed a compact cell layer entrapped within newly deposited extracellular matrix attached to the scaffolds’ fibers and between the porous cavities, that increased with culture time. After 7, 14, and 21 days, samples were collected and analyzed by qRT-PCR and GAG production. Cultured constructs in dual fluidic bioreactors differentiate regionally towards a tenogenic or chondrogenic fate dependent on exposure to the corresponding differentiation medium. SOX9 gene expression was upregulated (up to 50-fold compared to control) in both compartments, with a more marked upregulation in the cartilaginous portion of the scaffold, By day 21, the cartilage matrix marker, collage II, and the tendon specific marker, tenomodulin, were found to be highly upregulated in the cartilaginous and tendinous portions of the construct, respectively. In addition, GAG production in the treated constructs (serum-free) matched that in control constructs exposed to 10% fetal bovine serum, confirming the support of functional matrix formation in this system. In summary, our findings have validated this dual fluidic system as a potential platform to form the tendon enthesis, and will be optimized in future studies to achieve the fabrication of distinctly biphasic constructs.